A survey of cloud computing data integrity schemes: Design challenges, taxonomy and future trends. Issue 65 (March 2017) - Zafar, Faheem; Khan, Abid; Malik, Saif Ur Rehman; Ahmed, Mansoor; Anjum, Adeel; Khan, Majid Iqbal; Javed, Nadeem; Alam, Masoom; Jamil, Fuzel
Abstract: Cloud computing has gained tremendous popularity in recent years. By outsourcing computation and storage requirements to public providers and paying for the services used, customers can relish upon the advantages of this new paradigm. Cloud computing provides with a comparably lower-cost, scalable, a location-independent platform for managing clients' data. Compared to a traditional model of computing, which uses dedicated in-house infrastructure, cloud computing provides unprecedented benefits regarding cost and reliability. Cloud storage is a new cost-effective paradigm that aims at providing high availability, reliability, massive scalability and data sharing. However, outsourcing data to a cloud service provider introduces new challenges from the perspectives of data correctness and security. Over the years, many data integrity schemes have been proposed for protecting outsourced data. This paper aims to enhance the understanding of security issues associated with cloud storage and highlights the importance of data integrity schemes for outsourced data. In this paper, we have presented a taxonomy of existing data integrity schemes use for cloud storage. A comparative analysis of existing schemes is also provided along with a detailed discussion on possible security attacks and their mitigations. Additionally, we have discussed design challenges such as computational efficiency, storage efficiency, communication efficiency, and reduced I/O in these schemes. Furthermore, we have highlighted future trends and open issues, for future research in cloud storage security.